VD_FINDINFO Décision / 2015 / 709 vom 24. September 2015 - VD Tribunal cantonal (2015)
RISQUE DE FUITE, BRACELET ÉLECTRONIQUE, PAPIER DE LÉGITIMATION | 221 al. 1 let. a CPP (CH), 222 CPP (CH), 229 CPP (CH), 237 CPP (CH), 369 al. 3 CPP (CH)